A review of cardiac blackleg in cattle, and report of 2 cases without skeletal muscle involvement in Argentina. (November 2022) - Morrell, Eleonora L.; Odriozola, Ernesto; Dorsch, Matías A.; Fiorentino, María A.; Rivera, María E.; Poppenga, Robert; Navarro, Mauricio A.; Uzal, Francisco A.; Cantón, Germán
Blackleg is an infectious disease caused by Clostridium chauvoei . Cardiac blackleg has been reported in ruminants as an uncommon presentation of the disease; its pathogenesis is not understood completely. We include here a literature review of cardiac blackleg and a description of 2 cases in 12–15-mo-old feedlot steers in Argentina. Fourteen of 1, 190 steers died suddenly over a period of 10 d. Postmortem examinations were performed on 5 of these animals. Grossly, severe, diffuse, fibrinous pericarditis and pleuritis, multifocal necrohemorrhagic myocarditis, diffuse pulmonary congestion, mild splenomegaly, and moderate congestion of meningeal vessels were observed. No significant gross lesions were observed in the skeletal muscles of any animal. Histology was performed on 2 of the steers. The main microscopic features were necrotizing myocarditis with myriad intralesional gram-positive rods with subterminal spores plus fibrinosuppurative pericarditis and pleuritis. C. chauvoei was detected by immunohistochemistry and PCR in the myocardium of both animals. These findings confirm a diagnosis of cardiac blackleg in these 2 steers and presumptively in the other affected animals.